Management of lamellar keratoplasty in day-care unit - TianBishan; WangFeipeng; ZouQin; SuLijin (眼科学报, 2015)
Purpose: The management and efficacy of lamellar keratoplasty of 8 patients in day-care unit were summarized. Methods: The work flow and medical record of 8 cases undergoing corneal transplantation in day-care unit were retrospectively analyzed. Results: Eight patients were fully recovered. One case with fungal keratohelcosis were re-infected at postoperative 2 months and hospitalized. Conclusion: During lamellar keratoplasty in day-care unit, the work flow should be explicitly established and modified. The quality of patient selection, preoperative and postoperative nursing, follow-up after discharge should be carefully assured. In addition, nursing paperwork should be simplified, psychological nursing should be strengthened, and doctors and nurses should cooperate closely to enhance work efficiency.